(untitled) (AYUSHDHARA, 2022)
In past few years India has originated as one of the most important hubs for health tourism. There are several pull factors like excellent health facilities, low cost, easy accessibility, picturesque locations for excellent holiday etc. Globalized and modernized practices derived from Ayurveda traditions gave impetus to health tourism. Ayurvedic science is a monumental contribution of India to the world. Its main objective is preventive health care along with disease cure. The main attraction for tourists is rejuvenation promised by Yoga and Ayurvedic massage. Kerala is hub of health tourism just because of Panchkarma therapy. Despite it, ideal geographic location, salubrious climate and Samhita based approach are the other key factors. Other potential and developing fields in Ayurveda for Health Tourism are Swasthvritta (lifestyle modification), Pathya-apathya (dietary habits/Nutrigenomics), Garbha Sanskara (having a healthy and desired progeny), infertility management, Rasayana (rejuvenation), Vajikarana (aphrodisiac) etc. Ayurvedic medicines are herbal or herbo-mineral. Lack of identification, availability, proper collection and processing of herbs are the major hurdles that lead to contamination and affect the potency of preparation. Mineral compounds must be processed strictly following the guidelines mentioned in Ayurvedic texts. Otherwise, heavy metal contaminants left in the preparation might cause metal toxicity in consumers. Strict adherence to “Drug Standardization Protocols” is the need of hour by drug manufacturing units to remove the taboo of metallic toxicity and placebo for Ayurvedic preparations globally.